Investigating the Export Competitiveness of Indonesian Automobile in the Middle-East Countries - Abi Revyansah Perwira (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2021)
Since the automobile is one of Indonesia’s value-added commodities with the highest export potency, this paper attempts to investigate the competitiveness of Indonesian automobile in the Middle-east countries by employing the RSCA index and the EPD. The RSCA indices from the selected Middle-east countries reveal that the Indonesian automobile has a comparative advantage in Bahrain, Kuwait, Lebanon, Oman, Qatar, SA, and the UAE while Egypt and Jordan show a comparative disadvantage. The export competitiveness stability has medium to extreme fluctuations, particularly in Lebanon and the UAE, and shows an increasing trend only in Jordan and Qatar. The EPD matrix displays that Indonesia has Rising Star positions in Bahrain, Kuwait, Lebanon, Oman, and SA. While Falling Star positions are shown in Egypt, Jordan, Qatar, and the UAE. Indonesia should focus on SUV export development since this model has the highest demand in the Middle-east countries.